KOMODIFIKASI, DISABILITAS DAN TELEVISI - Bonardo Marulitua A (Cakrawala Jurnal Penelitian Sosial, 2016)
In Indonesia the presence of the mass media especially television has become animportant part in the life of the community. As agents of capitalism, television has beenproducing events capable of "deceiving" his audience interest. Not only as a product oftechnology, television has been transformed into an instrument that distribute widely thevalue. Even disability are understood as a social reality that taboo, has "wrapped" bytelevision and transformed into a commodity. Emerging economic interests behind theproliferation of the phenomenon of impressions, including disability-themed talk show inblack and white in TRANS7 featuring disability on Mulyana, an athlete swimming tunaDaksha.The theory of commodification and qualitative research methods with the approach tosemiotics Roland Barthes, the lead researcher on the understanding that the impressionson television which aired continuously have made the audience unable to contemplateevents that she saw. Any viewers take it for granted the knowledge-laden social valuesabout topics that she saw, including the existence of a practice of commodification andconsensus definition towards disability.Through tv footage, the production team talk show in black and white have labeling thatdisability TRANS7 is a strange creature, does not deserve the perfect, ridiculed,disgusting, sick, people affected by virus, can't live without the help of others so that mustbe isolated and dialienasi. In fact, labeling against disability progression away frommythology who appears in a number of cultures. Before the myth of disability meant assacred, sin, and the Savior. But in a talk show black and white TRANS7, disability thusbecome our Savior and “libido" satisfactory for the capitalists who always thirst forprofits.Keywords: Commodification, Disability, Semiotics, Television